Exploration of genetic diversity and drought tolerance potential of bread wheat genotypes at seedling stage using the multivariate analyses tools - Khan, Mueen Alam; Bashir, Ayesha; Ayyub, Muhammad Umar (Journal of Pure and Applied Agriculture, 2023)
Drought stress is one of the major limiting factors in plant growth. The endeavor of the present research was to identify bread wheat drought-tolerant genotypes by screening on the basis of seedling characteristics. The experiment was conducted during the cropping season (2021-2022) in the wire house of the Department of Plant Breeding & Genetics, Faculty of Agriculture & Environment, The Islamia University of Bahawalpur, Pakistan. Fifty-five genotypes were screened at the seedling stage under normal and drought stress conditions. Three treatments (T1, T2 and T3) were used with different polyethylene glycol (PEG-6000) solution concentrations i.e., (T1 was the controlled condition, T2 had 15% PEG solution, and T3 had 25% PEG solution). The results depicted the presence of significant differences among the genotypes related to drought tolerance and genetic diversity in response to the stress conditions using various morpho-physiological traits. Shoot fresh weight and chlorophyll content index were positively correlated under all treatments. Thus, the selection of these traits at the seedling stage would improve genetic gain for drought tolerance. Based on the results of principal component analysis (PCA), the promising genotypes identified were G19 (T1), G47 (T2) and G35 (T3). The identified traits could well serve as potential drought tolerance indicators and identified genotypes can be further utilized in future wheat breeding programs to develop high-yielding and drought-resilient genotypes.